ANALISIS PENGARUH TINGKAT KESEHATAN BANK TERHADAP KUALITAS LABA DENGAN PENDEKATAN RESIKO PADA BANK BUMN DI INDONESIA - Ni Kadek Ayu Oktayanti; Murtanto Murtanto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
This study aimed to analyze the effect of bank health variables which consists of NPL, Liquidity Risk, IRR, Deposit Ratio, FACR, ROA, ROE, NIM, ROA and CAR to Earnings Quality. The data used are the annual financial statements of four stateowned banks which are Bank BNI, Bank BRI, Bank Mandiri, and Bank BTN. The results of this study indicate that the only variable that partially has significant effect on earnings quality is NIM. While the NPL, Liquidity Risk, Deposit Ratio, FACR, ROE, ROA and CAR had no affect the earnings quality.